Thematic Progression in Students' Recount Texts : A Case Study in a Junior High School in Indramayu - Noviyanti, - (2015)
Penelitian ini mengenai analisis thematic progressions dari teks recount siswa di sebuah kelas di salah satu sekolah menengah pertama (SMP) di Indramayu, Jawa Barat, Indonesia. Penelitian ini bertujuan untuk menganalisa bagaimana siswa mengorganisir gagasan-gagasannya dalam teks. Penelitian ini menggunakan model kualitatif deskriptif mencakup karakteristik dari pendekatan studi kasus. Data penelitian ini diperoleh dengan mengumpulkan hasil tulisan siswa di kelas. Enam hasil tulisan siswa diseleksi dari tiga tingkat prestasi siswa-rendah, sedang, dan tinggi. Untuk kerangka analisis teks, penelitian ini menggunakan teori Systemic Functional Linguistics, khususnya thematic progressions yang dikembangkan oleh Bloor & Bloor (2005), Eggins (2004), Emilia (2014), Fries (1994; 1995a; 1995b), dan Halliday & Mathiessen(2004); dan cohesion and coherence yang dijelaskan oleh Butt, et.al., (2000), Droga, (2003), Eggins, (2004), Emilia, (2014), Gerot & Wignell, (1994), dan Halliday & Hasan, (1976). Hasil dari penelitian ini menunjukkan bahwa semua tingkat prestasi siswa telah memahami tujuan utama dan struktur skematis dari teks recount; kekonsistensian thematic progression dimana pola thematic progression yang paling sering muncul adalah pola reiteration, diikuti oleh pola zigzag; dan thematic progression memegang sebuah peranan penting dalam mewujudkan teks yang memiliki keterpaduan dan keterhubungan. Berdasarkan penemuan tersebut, direkomendasikan bahwa para guru harus lebih memerhatikan manfaat dari penggunaan analisis thematic progressions yang diaplikasikan dalam proses pembelajaran bahasa Inggris untuk mendapatkan pengawasan dan perkembangan yang lebih baik. Selain itu, disarankan bahwa peneliti selanjutnya dapat menganalisa jenis teks lain atau menganalisa alat cohesive lainnya di luar thematic progressions. Keywords: Thematic Progressions, Cohesion and Coherence, Recount Text This study is concerned with analyzing thematic progressions of students' recount texts in one class of one public junior high school in Indramayu, West Java, Indonesia. This study aims to investigate how the students organize their ideas in the texts. This study employs a qualitative research design embracing the characteristics of a case study approach. The data were obtained by collecting students' writing products in the class. Six students' writing products were selected from three different levels of achievement-low-, mid-, and high- achiever. For the framework of the text analysis, this study draws on Systemic Functional Linguistics theory, especially of thematic progressions developed by Bloor & Bloor (2005), Eggins (2004), Emilia (2014), Fries (1994; 1995a; 1995b), and Halliday & Mathiessen (2004); and cohesion and coherence elaborated by Butt, et al., (2000), Droga, (2003), Eggins, (2004), Emilia, (2014), Gerot & Wignell, (1994), and Halliday & Hasan, (1976). The results show that all students' texts from all levels had acquired the main purpose and the schematic structure of a recount text. Moreover, in terms of thematic progression consistency, the most occurrence of thematic progression pattern is the reiteration pattern, followed by the zigzag pattern. These thematic progressions played a significant role in supporting the cohesion and the coherence of the texts. Based on the findings, it is recommended that the teachers pay more attention to advantages of employing thematic progressions analysis applied in English learning process to allow students to gain a better control of text organization and development. Besides, it is also suggested for further researchers to investigate the other texts or to analyze the cohesive devices beyond thematic progressions. Keywords: Thematic Progressions, Cohesion and Coherence, Recount Text